Thibault Girard. L’oblique dans le monde grec. Concept et imagerie - Rodríguez Pérez, Diana (Journal of Greek Archaeology, 2016)
Concepts such as oblique, vertical or horizontal are so rooted in our daily vocabulary that an explanation of the terms seems superfluous, for these are—or so we think—rather evident and unequivocal words that serve to define a state or a quality. Nevertheless, as the book under review elucidates, the reality is that for ancient Greeks these concepts were not as neatly defined as they are for us today, and that ancient Greek even lacks the words which would unequivocally correspond to our notions of oblique, vertical, and horizontal.